Dorothea Tanning’s Reimagining of the Maternal - Glăvan Gabriela (Romanian Journal of English Studies, 2021)
Dorothea Tanning’s longstanding interest in the maternal element completes the artist’s complex relationship to femininity and the female experience, turning them into essential themes in her oeuvre. I shall explore the particular manner in which the American Surrealist integrates and transforms the notion of motherhood in her art. I shall also argue that Tanning’s works as a writer offer an original insight into this cardinal theme in western art, as she dismantles common tropes and refashions them into a new, unusual language.